PUBLIC POLICY ANALYSIS OF DECENTRALIZED NATIONAL ELECTRONIC HEALTH RECORDS USING BLOCKCHAIN TECHNOLOGY - Mulyaningsih Mulyaningsih; Nurul Huda; Nina Anis (Journal of World Future Medicine, Health and Nursing, 2026)
National electronic health record (EHR) systems face persistent challenges related to interoperability, data security, and fragmented governance structures, particularly within centralized architectures that limit real-time data exchange across healthcare institutions. This study aims to analyze public policy implications of implementing decentralized national EHR systems using blockchain technology, with emphasis on governance transformation, regulatory alignment, and system performance. A qualitative-dominant mixed-methods approach is employed through comparative policy analysis, secondary data evaluation, and stakeholder interpretation. Results indicate that blockchain-based EHR systems significantly improve interoperability (88% vs 62%), reduce data breach incidence (3 vs 18 cases per million records), and enhance patient data accessibility (score 91 vs 65). Inferential findings confirm statistically significant improvements in system efficiency and governance performance. The study concludes that decentralized blockchain-enabled EHR systems offer substantial advantages over centralized models, not only in technical performance but also in reinforcing transparency, trust, and data sovereignty within national health governance frameworks, while requiring adaptive regulatory reforms for sustainable implementation.